Techno-economic analysis of biorefinery scenarios for scFOS, ethanol, tryptophan, erythritol and collagen production from sugarcane - Klaver, Monique (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.